2008
DOI: 10.5565/rev/ensciencias.3687
|View full text |Cite
|
Sign up to set email alerts
|

Diez años de evaluación de la enseñanza-aprendizaje de la mecánica de Newton en escuelas de ingeniería españolas. Rendimiento académico y presencia de preconceptos

Abstract: El Force Concept Inventory (FCI) ha estado siendo utilizado para evaluar a alumnos de primer curso de escuelas de ingeniería de distintas universidades españolas desde su publicación en 1992. Sus resultados se han comparado con los procedentes de algunas universidades estadounidenses donde el FCI también había sido aplicado. A partir de estos resultados -expuestos en el artículo- se ha podido detectar un escaso nivel de conocimiento del concepto de fuerza, un bajo rendimiento académico y la persistencia de pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
2
1
2
Order By: Relevance
“…The global rFCI results are shown in Table 2. Although these results are not directly comparable with data from other studies, because a reduced FCI was used, the scores and Hake's normalized gain was similar to the ones given by Covián Regales and Celemín Matachana (2008) for other engineering High Schools in Spain. c, d and e).…”
Section: Overall Rfci Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…The global rFCI results are shown in Table 2. Although these results are not directly comparable with data from other studies, because a reduced FCI was used, the scores and Hake's normalized gain was similar to the ones given by Covián Regales and Celemín Matachana (2008) for other engineering High Schools in Spain. c, d and e).…”
Section: Overall Rfci Resultscontrasting
confidence: 54%
“…Concept surveys results have shown that traditional instruction (lecture-demonstration) fails badly in meeting a minimal performance standard for mechanics (Covián Regales and Celemín Matachana, 2008;Hestenes, 1997). Misconceptions seem to be persistent regardless of the teacher, the methodology (Hestenes et al, 1992), the country and the students' knowledge (Mora and Herrera, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• 7 3 9 • implementada en el aula de clase, alto (0.7 < g ≤ 1), medio (0.3 < g ≤ 0,7), y bajo (0 ≤ g ≤ 0.3) (Stewart, & Stewart, 2010). España (Covián & Celemín, 2008).…”
Section: Instrumentounclassified
“…Desde hace un tiempo, gracias a los resultados de investigaciones en la Didáctica de las Ciencias Naturales (Adúriz Bravo e Izquierdo Aymerich, 2002;Carretero, 2009aCarretero, , 2009bDriver et al, 1985;Pozo y Gómez Crespo, 1998a;Solbes, 2009;Viennot, 2002), y a la preocupación compartida por los resultados de la retención y aprobación en los cursos de Física de los dos primeros años universitarios (Covián Regales y Matachana, 2008;Cravino y Lopes, 2003;Llancaqueo Henríquez et al, 2007;Pozo y Gómez Crespo, 1998b;Santos Benito y Gras-Martí, 2003) existe un interés creciente en los docentes universitarios por implementar propuestas que sean novedosas y motivadoras para los alumnos, ya sea en carreras de Ciencias, Ingeniería o Profesorado en Ciencias, y que a la vez promuevan el aprendizaje significativo de las teorías, modelos, leyes y conceptos de la Física.…”
Section: Motivaciónunclassified